A sign preserving mixed finite element approximation for contact problems - Hild, Patrick (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with the frictionless unilateral contact problem (i.e., a Signorini problem with the elasticity operator). We consider a mixed finite element method in which the unknowns are the displacement field and the contact pressure. The particularity of the method is that it furnishes a normal displacement field and a contact pressure satisfying the sign conditions of the continuous problem.
Keywords: variational inequality; positive operator; averaging operator; contact problem; Signorini problem; mixed finite element method